Segmentation of cell clumps for quantitative analysis - Li, S (IEEE, 2010)
The increasing amounts of microscopy data generated in cell biology requires the development of automated tools for the quantitative analysis of images. Clumps of cells are difficult to segment due to the frequent lack of clear boundaries between cells and are often ignored, but communication between cells is an intrinsic part of the response of cells to their environment. In addition cells often show a large variation in their responses, even within a clump, and an accurate segmentation is therefore vital to prevent the unwanted averaging of measurements over multiple cells. Here we present a method for segmenting clumps of cells by using a multi-scale ridge filter to enhance unclear boundaries. A multi-phase level set method incorporating a region competition term is used to identify a boundary for each cell based on the ridge filter response.